“UNTIMELINESS” AND DE-(CON)STRUCTION. FOOTNOTES TO NIETZSCHE AND DERRIDA - Zsuzsanna LURCZA (Studia Universitatis Babeș-Bolyai. Philosophia)
Although the title of the study contains even two questions, who is Zarathustra? and who is the »Who«?, it cannot be claimed that the main goal of this study is to answer them. In particularly, it cannot be claimed that these questions are answerable at all. The questions serve as leitmotif for displaying the untimely program of Nietzsche and the deconstruction of Derrida, showing analogy aspects between them, which are related to the critique of western metaphysics and its language as well as to de(con)struction of the concepts of subject and identity.